Strategy for the Institutional Development of the Bina Jaya Tani Farmers’ Economic Organization (KEP) in Karawang Regency - Siti Mariyani; Ana Melani; Zulfa Nur Auliatunnisa’; Tirta Anugerah (Universitas Muhammadiyah Malang, 2026)
Agricultural activities involve farmer organizations that support farmers’ socioeconomic activities. Farmer economic organizations (KEPs) play a significant role in promoting community self-reliance and food security; however, in developing countries, the institutional framework for food security remains weak. This community faces challenges such as limited market access, necessitating development efforts to reach broader markets. The objective of this study is to formulate a development strategy for the KEP to support farmers’ welfare in Karawang Regency. The method used is quantitative descriptive. Informants were selected through purposive sampling, specifically the chairperson and secretary of this community. Data analysis employed quantitative descriptive analysis using a three-stage process for strategic planning formulation. The research results indicate that the strategy implemented by KEP Bina Jaya Tani is a growth-oriented strategy that optimizes its strengths and opportunities, namely: (1) Developing rice products using attractive packaging and a variety of rice types; (2) Increasing production capacity by leveraging easy access to raw materials from farmer groups; (3) Expanding the reach of premium rice products to the main rice markets in Karawang and surrounding areas; (4) Developing location-based digital marketing with attractive packaging; and (5) Integrating agricultural technology to efficiently improve product quality.